Effects of maternal bisphenol A diglycidyl ether exposure during gestation and lactation on behavior and brain development of the offspring. (April 2020) - Miyazaki, Ikuko; Kikuoka, Ryo; Isooka, Nami; Takeshima, Mika; Sonobe, Kanau; Arai, Rei; Funakoshi, Hidemaru; Quin, Kyle E.; Smart, Jonathan; Zensho, Kazumasa; Asanuma, Masato
Abstract: Bisphenol A diglycidyl ether (BADGE) is an epoxy resin used for the inner coating of canned food and beverages. BADGE can easily migrate from the containers and become a contaminant. In this study, we examined the effects of BADGE exposure to the dams on the behavioral, structural, and developmental abnormalities in the offspring. Female pregnant mice were fed with a diet containing BADGE (0.15 or 1.5 mg/kg/day) during gestation and lactation periods. In an open field test, the time spent in the corner area significantly increases in male mice of high-dose BADGE group at 5 weeks old. The histological analysis using offspring brain at postnatal day 1 delivered from BADGE (1.5 mg/kg/day)-treated dams demonstrates that positive signals of Forkhead box P2- and COUP-TF interacting protein 2 are restricted in each cortical layer, but not in the control brain. In addition, the maternal BADGE exposure reduces nestin-positive fibers of the radial glia and T-box transcription factor 2-positive intermediate progenitors in the inner subventricular zone. Furthermore, a direct BADGE exposure promotes neurite outgrowth and neuronal connection in the primary cultured cortical neurons. These data suggest that maternal BADGE exposure can accelerate neuronal differentiation in fetuses and induce anxiety-like behavior in juvenile mice. Graphical abstract: Image 1 Highlights: Maternal BADGE exposure induces anxiety-like behavior in pups. Maternal BADGE exposure accelerate neuronal differentiation in the cortex of fetuses. Treatment with BADGE promotes neurite outgrowth in cultured cortical neurons.